The Effect Of The Completeness Of Financial Statements And Fiscal Stress On The Human Development Index Through The Regional Financial Performance - Anggraeni, Rina; Kiswanto, Kiswanto (Accounting Analysis Journal, 2018)
Penelitian ini bertujuan untuk memperoleh bukti empiris mengenai pengaruh Kelengkapan Laporan Keuangan dan Fiscal Stress terhadap Indeks Pembangunan Manusia (IPM) dengan Kinerja Keuangan Pemerintah sebagai Variabel Intervening. Populasi penelitian, yaitu pemerintah daerah Kabupaten/Kota di Provinsi Jawa Tengah tahun 2013-2015. Teknik pengambilan sampel menggunakan metode sampel jenuh (sensus) yaitu penggunaan seluruh populasi dengan jumlah 35 kabupaten/kota. Teknik analisis yang digunakan adalah analisis Structural Equation Model (SEM) menggunakan AMOS 21. Hasil penelitian ini menunjukan bahwa kelengkapan laporan keuangan mempengaruhi kinerja keuangan pemerintah secara signifikan. Kinerja keuangan daerah mempengaruhi indeks pembangunan manusia secara signifikan. Sedangkan fiscal stress tidak berpengaruh signifikan terhadap kinerja keuangan daerah. Hasil penelitian ini juga membuktikan bahwa kinerja keuangan mampu memediasi hubungan Kelengkapan Laporan Keuangan terhadap IPM. Berdasarkan hasil penelitian, dapat disimpulkan bahwa indeks pembangunan manusia dipengaruhi oleh kelengkapan laporan keuangan, dan kinerja keuangan daerah. This research aims to obtain the empirical evidences regarding the influence of the Completeness of financial statements and fiscal stress on human development index with local government financial performance as an intervening variable. The population in this research is Districts / cities in Central Java Province in 2013-2015. The method used is a saturated sample (census) that is the use of the entire population with the number 35 districts / cities. The analytical technique used is analysis of Structural Equation Models (SEM) with AMOS 21. The results of this study indicate that the Completeness of financial statements affects positively and significantly on the government's financial performance. Financial performance of the regions affects the human development index positively and significantly. Fiscal stress does not have a significant influence to the financial performance of the region. The results of the study also proved that the Completeness of financial statement has a significant influence to human development index of the local financial performance. Based on the research result, it can be concluded that human development index influenced by the Completeness of the financial statement and financial performance.